The architecture on land and its construction techniques, millenary tradition that is reborn (2018)
In the context of sustainable development, the use of materials of low environmental impact in the activities inherent to the construction of houses plays an important role when it comes to reducing waste pollution. The alternative materials to be used in the various construction processes, besides being totally renewable, they must be reusable, available locally and have little or no energy expenditure in its extraction, preparation and application. The Bio resources or Eco materials meet these requirements, of which land as ancestral material used in millenary construction techniques, it becomes the most feasible alternative for its use as a construction material to replace the conventional ones. The main objective is the literary review of articles published in reliable databases, whose research topic was based on the analysis and use of land and natural materials for application in housing construction. The articles were categorized, analyzed and integrated into a synthesized structure to extract the important aspects in the thematic introduction, the constructive techniques, the results of the processes carried out and finally, the conclusions on the constructive implementation of the elements studied. In this way it offers information of interest to people who want to delve into the subject investigated.